A novel algorithm for strengthening of chaos based S-Box generators - Özkaynak, Fatih; Özer, Ahmet Bedri (My University, 2010)
Many chaos based S-Box generator algorithms have been proposed utilizing a strong relationship between the science of chaos and cryptography. However these algorithms have a strong cryptographic features are dependent on the selected chaotic system. The proposed algorithm in this study the dependence of chaotic systems is eliminated. The results of the analysis show that the proposed algorithm is a highly reliable system suitable for secure communication.
Kaos tabanli S-Box üreteçlerinin güçlendirilmesi için yeni bir algoritma
2010 7th National Conference on Electrical, Electronics and Computer Engineering, ELECO 2010 -- 2 December 2010 through 5 December 2010 -- Bursa -- 83834
Keywords: Algorithms; Cryptography; Electrical engineering; Highly reliable systems; Novel algorithm; Secure communications; Chaotic systems